Aprendizagem de língua inglesa por alunos com dificuldades de aprendizagem: evidências de conhecimento e apropriação da língua alvo - Ferrari, Crissiane Rosa (Universidade do Vale do Rio dos Sinos, 2012)
The learning disabilities (LDs) are present in the regular teaching context embracing a significant number of students in one or more subjects. Most of the times, they are an obstacle to the development of the educational learning, once considered the age group and the level of education of the students, resulting on a performance below the expectations and, in many cases, having the child to repeat the grade. Given those facts, studies that reflect both on learning disabilities by virtue of the student to present what is called disabled person, as well as on learning disabilities considered nonspecific, that emerge as consequences to the school and/or family environment of the child, to the kind of instruction received, to their economical and social conditions, to the personal variables, among others. This research, immerse in this reflection, is constituted as an action research, in which data were generated through interviews, collection of activities and video recordings during the implementation of a teaching proposal with the English language. Thus, in a first moment, it is centered on the learning of Foreign Language by students with LDs in a regular school context, implementing a proposal of work, based on the sociocultural theory by Vygotsky, which, together with concepts of literacy, evinces the learning of these students regarding their domain of the language. The focus is on the role of the English language in such contexts, once this researcher has verified a positive involvement of those students towards the learning of this language. The results of this study indicate that what the school defines as learning disabilities, in fact, does not correspond to the learning of the target language showed by students surrounded by a proper environment for learning, which respects their specificities and considers their previous knowledge about the subject that will be approached, giving support to the construction of knowledge through interaction. Given such findings, we highlight that the concept of LDs must be rethought in schools’ routine, for, if there are not pedagogical practices that aim the promotion of learning, instead of the latter being valued, the difficulties will stand out. We understand, therefore, that the focus on the difficulties does not have to be assumed by the school community, because, as this study shows, the learning of the English language is unveiled all along the investigated process.
Keywords: Dificuldades de aprendizagem; Língua Inglesa; Teoria sociocultural; Learning disabilities; English language; Sociocultural theory; ACCNPQ::Lingüística, Letras e Artes::Lingüística